Intraperitoneal delivery of nanoparticles for cancer gene therapy - Hallaj-Nezhadi, Somayeh; Dass, Crispin; Lotfipour, Farzaneh (Future Medicine, 2013)
Nanoparticle-based gene delivery systems may be more efficient for administration of therapeutic genes to solid tumors and cancer metastases, owing to the numerous advantages in terms of enhanced tissue penetrability, improved cellular uptake and targeted gene delivery to the cells of interest compared with other gene delivery systems. Intraperitoneal (IP) delivery of therapeutic agents offers special merits because of the anatomical situation of peritoneum for local cancer therapy. Via the IP administration route, it is possible to target the therapeutic agents exactly to the target cells and protect healthy tissues outside the peritoneal cavity from side effects. IP delivery could be applicable for the treatment of disorders of organs in the peritoneal cavity covered with peritoneum and subperitoneal connective tissue, including cancers such as ovarian and gastric. The goal of this article is to review the current state of IP delivery of nanoparticles for cancer gene therapy.